Efficacy of Biochar Application with Different Nutrient Sources on Okra Production in Puranchour, Kaski, Nepal - Subedi, Arjun; Sapkota, Prativa (Nepalese Horticulture, 2025)
Agriculture plays a vital role in the economy and encounters issues such as soil degradation and climate change, making the adoption of biochar highly promising. This study aimed to investigate the impact of biochar combined with various nutrient sources on the growth and yield of okra (Abelmoschus esculentus L.) in Puranchour, Kaski, Nepal. A field experiment was conducted from June to September, 2024 using a randomised complete block design with five treatments replicated four times: i) Control (C); ii) Biochar @ 8 ton/ha (BC); iii) Biochar @ 8 ton/ha + Vermicompost @ 10 ton/ha (BCVC); iv) Biochar @ 8 ton/ha + Cattle Urine (1:5) (BCCU); and v) Biochar @ 8 ton/ha + Mustard Cake @ 100 kg/ha (BCMC). Results indicated that the BCVC treatment significantly enhanced plant height (28.55 cm & 128.80 cm), leaf number (12.80 & 28.30), node count (11.95 & 19.30), and stem girth (0.60 cm & 1.10 cm) at 45 and 75 days after sowing (DAS), respectively. It also promoted early germination (10.25 days), flowering (44.00 days), and fruiting (50 days) compared to other treatments, with the control showing the least favourable results. Yield parameters such as fruit length (15.55 cm), fruit girth (2.22 cm), number of fruits per plant (17.50), individual fruit weight (17.00 g), and yield (13.75 mt/ha) were highest in BCVC and lowest in the control. The findings highlight the synergistic benefits of biochar with organic amendments, suggesting its potential as a sustainable solution to improve soil fertility and crop productivity in Nepal’s varied agro-climatic conditions.